2016
DOI: 10.1073/pnas.1604348113
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal domain of complexin independently activates calcium-triggered fusion

Abstract: Complexin activates Ca 2+-triggered neurotransmitter release and regulates spontaneous release in the presynaptic terminal by cooperating with the neuronal soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs) and the Ca 2+ -sensor synaptotagmin. The N-terminal domain of complexin is important for activation, but its molecular mechanism is still poorly understood. Here, we observed that a split pair of N-terminal and central domain fragments of complexin is sufficient to activate Ca 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 78 publications
1
55
0
Order By: Relevance
“…Similarly, knockdown in cultured cortical neurons increases spontaneous release, although knockout of complexin in mice only affects spontaneous release depending on the particular neuronal cell type (12,16,27,28). A split pair of N-terminal and central domain fragments of Cpx is sufficient to activate Ca 2+ -triggered release using our reconstituted single-vesicle fusion assay, suggesting that the N-terminal domain acts as an independent module within the synaptic fusion machinery (30). Moreover, the Cpx accessory domain can be entirely eliminated, and the resulting split pair of Cpx constructs still activates Ca 2+ -triggered fusion (i.e., a clamping process is not required for activation) (30).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Similarly, knockdown in cultured cortical neurons increases spontaneous release, although knockout of complexin in mice only affects spontaneous release depending on the particular neuronal cell type (12,16,27,28). A split pair of N-terminal and central domain fragments of Cpx is sufficient to activate Ca 2+ -triggered release using our reconstituted single-vesicle fusion assay, suggesting that the N-terminal domain acts as an independent module within the synaptic fusion machinery (30). Moreover, the Cpx accessory domain can be entirely eliminated, and the resulting split pair of Cpx constructs still activates Ca 2+ -triggered fusion (i.e., a clamping process is not required for activation) (30).…”
Section: Discussionmentioning
confidence: 74%
“…A split pair of N-terminal and central domain fragments of Cpx is sufficient to activate Ca 2+ -triggered release using our reconstituted single-vesicle fusion assay, suggesting that the N-terminal domain acts as an independent module within the synaptic fusion machinery (30). Moreover, the Cpx accessory domain can be entirely eliminated, and the resulting split pair of Cpx constructs still activates Ca 2+ -triggered fusion (i.e., a clamping process is not required for activation) (30). Cpx has two conformations when bound to the ternary SNARE complex (55,56), one of which induces a conformational change at the membrane-proximal C-terminal end of the ternary SNARE complex that specifically depends on the N-terminal, accessory, and central domains of Cpx (56).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, the complex nature of cellular synapses consisting of dynamic and dense networks of protein-protein and protein-membrane interactions makes it difficult to study the synaptic fusion protein machinery in vivo. Therefore, we used a bottom-up approach where we reconstituted synaptic proteins into liposomes in a stepwise fashion: Synaptobrevin-2 and Syt1 were reconstituted into liposomes with a defined synthetic lipid composition that mimics synaptic vesicles (referred to as "SV vesicles"), and syntaxin-1A and SNAP-25A were reconstituted into liposomes with a lipid composition that mimics the plasma membrane obtained from lipid brain extracts (referred to as "PM vesicles") (19).…”
mentioning
confidence: 99%
“…Some characteristics of the in vivo function of complexin have successfully been reconstituted (Lai, et al, 2014;Giraudo, et al, 2009;Malsam, et al, 2012;Lai, et al, 2016); however, biochemical studies of complexin and SNARE proteins have not revealed a clear mechanism by which complexin inhibits spontaneous fusion. The EPR and NMR spectroscopy, fluorescence anisotropy, and TIRF microscopy to characterize the interaction between complexin, SNAREs, and the lipid bilayer.…”
Section: Discussionmentioning
confidence: 99%